STUDI KOMPARATIF TENTANG NILAI PERUSAHAAN DAN PROFITABILITAS BERDASARKAN KINERJA SOSIAL - Siti Madaniah; Rosi di (Jurnal Ilmiah Mahasiswa FEB, 2012)
Many private corporation now develop their performance based on Corporate Social Responsibility (CSR). CSR practices are no longer treat as a cost but as an investation of those corporate. Management believed that corporate sustainability would be much more saver if they put the concern on social and environmental dimensions, alongside with consumer believe on socialy responsible corporate. Some study have proved this trend that the higher social performance corporate tend to show the higher corporate value. This research is a descriptive quantitative, using comparative paradigm. Paired sampel t-test statistical analisys used to analize the data. Sampel employ for this analisys are participant corporate of ISRA treated as two different group consist of award winner (8 corporate) and non award (8 corporate). The result of this research indicate that: 1) the differences was significantly exist between two group based on corporate value and 2) the differences wasn’t significantly exist between two group based on profitability.   Keywords:       social performance, corporate value, profitability, Indonesia Social Responsibility Award (ISRA)